Environmental correlates of health-promoting leisure physical activity in persons with multiple sclerosis using a social cognitive perspective embedded within social ecological model - Silveira, Stephanie L. (Prev Med Rep, 2019)
There is abundant evidence for the benefits of physical activity (PA) among persons with multiple sclerosis, however only 20% of persons with MS engage in sufficient PA. This cross-sectional study examined features of the built environment, social environment, and individual as hierarchical correlates of PA in persons with MS from a social-cognitive theory (SCT) perspective embedded within a social-ecological model (SEM). Five hundred eighty eight persons with MS completed an online survey between September 2018–January 2019 including: demographics, Patient Determined Disease Steps (PDDS), abbreviated Neighborhood Walkability Scale (NEWS-A), Social Provisions Scale (SPS), Exercise Self-Efficacy Scale (EXSE), and Godin Leisure-Time Exercise Questionnaire (GLTEQ). Correlation analyses were used to examine associations among NEWS-A subscales, SPS, EXSE, PDDS, Employment, Education and GLTEQ. We then conducted hierarchical, linear regression analysis whereby we regressed GLTEQ with PDDS, Education, and Employment (Step 1), NEWS-A subscales (Step 2), SPS (Step 3), and EXSE (Step 4) based on a SEM. Land-use mix diversity, land-use mix access, aesthetics, crime, SPS, EXSE, and PDDS correlated with GLTEQ. PDDS was a significant correlate of GLTEQ in Step 1 (β = −0.37;R(2) = 0.15). Aesthetics (β = 0.08) and PDDS (β = −0.33) were significant correlates of GLTEQ in Step 2 (R(2) = 0.18). SPS (β = 0.23) and PDDS (β = −0.30) were significant correlates of GLTEQ in Step 3 (R(2) = 0.23). The final model in Step 4 identified PDDS (β = −0.11), aesthetics (β = 0.07), SPS (β = 0.09), and EXSE (β = 0.54) as correlates of GLTEQ (R(2) = 0.43). Such results may inform the design of multi-level interventions that target environmental and individual correlates of PA consistent with the SEM framework and guided by SCT.